A lotus root inspired implant system with fever responsive characteristics and 3D printing defined nano-antibiotic release patterns. Issue 80 (15th August 2016) - Ding, Xingwei; He, Xiaoyi; Xue, Chaowen; Wu, Changwen; Xie, Lin; Chen, Tingtao; Wei, Junchao; Cheng, Xigao; Wang, Xiaolei
Abstract : Lotus root imitated scaffolds were fabricated with several critical releasing parameters could be prearranged. Furthermore, when postoperative infection caused hyperthermia occurred, the inner drugs, could be spontaneously released. Abstract : Lotus root imitated implant scaffolds with highly flexible drug release patterns were fabricated. Several critical release parameters could be conveniently prearranged through creating a precisely customized inner chamber via 3D printing. Furthermore, when postoperative infection caused hyperthermia, the inner drugs could be spontaneously released to inhibit the invasive pathogens.